2002
DOI: 10.1080/1355785022000042024
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Self-reported Lack of Access to a Regular Doctor: A Population-based Study

Abstract: Self-reported lack of access to a regular doctor was significantly higher among men born in Nordic countries, Arabic countries and other countries compared to men born in Sweden, but all these differences disappeared after adjument for age and in the multivariate analysis. Women born in Arabic speaking countries and other countries lacked access to a regular doctor to a significantly higher extent compared with women born in Sweden, and these differences remained in the multivariate analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The 26.7% proportion of individuals born in other countries than Sweden rather seems to represent a slight overrepresentation of the foreign born part of the Malmö population in the age brackets included in this study. Furthermore, the distribution of the country of origin categories is similar to that observed in the general Malmö population for all the ethnic groups (Axén and Lindström, 2002;Malmö Statistical Yearbook 1994). There may theoretically also be some underrepresentation of those having lived for a comparatively short period in Sweden.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The 26.7% proportion of individuals born in other countries than Sweden rather seems to represent a slight overrepresentation of the foreign born part of the Malmö population in the age brackets included in this study. Furthermore, the distribution of the country of origin categories is similar to that observed in the general Malmö population for all the ethnic groups (Axén and Lindström, 2002;Malmö Statistical Yearbook 1994). There may theoretically also be some underrepresentation of those having lived for a comparatively short period in Sweden.…”
Section: Discussionsupporting
confidence: 70%
“…The literature on different aspects of social participation in Arabic speaking countries is extremely scarce, but another study based on the public health survey in Malmö 1994 that concerned ethnic differences in the lack of access to a regular doctor showed that women born in Arabic speaking countries and all other countries reported lack of access to a regular doctor to a significantly higher extent than the female reference group born in Sweden. In contrast, no such ethnic differences were observed among men (Axén and Lindström, 2002). Language (in this case Swedish as opposed to Arabic) was not included in the 1994 public health questionnaire.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in our study both single fathers and single mothers had worse financial status, which again had a major impact on health (both fathers and mothers) [19,20] and healthcare utilization (single mothers only) [14,18]. Moreover, single mothers were more often of nonSwedish origin, which in turn may be associated with poorer health [21,22] and inadequate healthcare utilisation [16,23]. Finally, level of education influenced both health and healthcare utilization.…”
Section: Uneven Distribution Of Sociodemographic and Socioeconomic Chmentioning
confidence: 70%
“…It might be argued that Sweden is a welfare state with equal access to healthcare. However, a previous study from Malmö has shown important socioeconomic and ethnic differences in access to healthcare, particularly among women [17]. Material deprivation [18] of a neighbourhood may thus also explain area differences in non-attendance for mammographic screening.…”
Section: Introductionmentioning
confidence: 96%